Decreased affinity for oxygen of cytochrome-c oxidase in Leigh syndrome caused by SURF1 mutations - Pecina, Petr; Gnaiger, Erich; Zeman, Jirí; Pronicka, Ewa; Houstek, Josef (American journal of physiology. Cell physiology, 2004)
Mutations in the gene SURF1 prevent synthesis of cytochrome-c oxidase (COX)-specific assembly protein and result in a fatal neurological disorder, Leigh syndrome. Because this severe COX deficiency presents with barely detectable changes of cellular respiratory rates under normoxic conditions, we analyzed the respiratory response to low oxygen in cultured fibroblasts harboring SURF1 mutations with high-resolution respirometry. The oxygen kinetics was quantified by the partial pressure of oxygen (PO2) at half-maximal respiration rate (P50) in intact coupled cells and in digitonin-permeabilized uncoupled cells. In both cases, the P50 in patients was elevated 2.1- and 3.3-fold, respectively, indicating decreased affinity of COX for oxygen. These results suggest that at physiologically low intracellular PO2, the depressed oxygen affinity may lead in vivo to limitations of respiration, resulting in impaired energy provision in Leigh syndrome patients.
Keywords: Leigh Disease; Membrane Proteins; Humans; proteiny; Oxygen Consumption; Proteins; mutace; lidé; deficit cytochrom-c-oxidázy; Mitochondrial Proteins; Cells, Cultured; mitochondriální proteiny; Leighova nemoc; Oxygen; kyslík; respirační komplex IV; kultivované buňky; spotřeba kyslíku; membránové proteiny; fibroblasty; Electron Transport Complex IV; Mutation; Cytochrome-c Oxidase Deficiency; Fibroblasts